Development of an item pool for a patient reported outcome measure of resilience for people living with dementia - Jennifer Rhiannon Roberts; Catherine Anne MacLeod; Zoe Hoare; Mary Pat Sullivan; Emilie Brotherhood; Joshua Stott; Gill Windle (Journal of Patient-Reported Outcomes, 2023)
Abstract Background and objectives Policies to support people living with dementia increasingly focus on strengths-based approaches, highlighting the importance of building resilience. This research responds to the lack of a suitable resilience measure for people with dementia. It develops a pool of items to inform a new measure of resilience for this population. Methods A conceptual model and associated data informed the item generation of the draft resilience measure. Regular meetings with professionals (n = 7) discussed response-scale formatting, content and face validity, leading to refinement and item reduction. Cognitive interviews with people living with dementia (n = 11) then examined the face and content validity of items and the suitability of response-scale formatting. These two phases informed subsequent revision and further item reduction of the resilience measure. Results The first item generation exercise led to 140 items. These were independently assessed by the professionals and this refinement reduced the measure to 63 items across 7 domains of the conceptual model (psychological strengths; practical approaches for adapting to life with dementia; continuing with hobbies, interests and activities; strong relationships with family and friends; peer support and education; participating in community activities; the role of professional support services). Cognitive interviews explored the 63 items with people living with dementia. Detailed feedback led to items removed due to difficulty with (a) understanding (N = 7); (b) answering (n = 11); (c) low preference for that item (n = 6); and (d) presence of a preferred item within a cluster of similar questions (n = 4). Items were amended to enhance clarity/conciseness (n = 19) leading to a final 37-item pool. Conclusion Established methods for measurement development included the expertise of people with dementia and led to the generation of a set of items for a new resilience measure that were understandable and acceptable to this target population. This 37-item pool reflects the conceptual understanding of resilience in dementia as being derived across individual, community and societal level resources.